Mulch Based No‐Tillage and Compost Effects on Nitrogen Fertility in Organic Melon. (1st July 2018) - Tittarelli, Fabio; Campanelli, Gabriele; Leteo, Fabrizio; Farina, Roberta; Napoli, Rosario; Ciaccia, Corrado; Canali, Stefano; Testani, Elena
Abstract : Core Ideas: No‐till roller crimper was confirmed to be a suitable technology for weed management. Melon yield and quality declined under no‐till roller crimped barley. Compost application and agro‐ecological service crop cultivation showed high potential carbon sink effect. Cropping systems and varieties should be adapted to no‐till roller crimper. Agro‐ecological service crop management and compost should be combined to fit the specific local conditions. Soil fertility management in organic farming systems relies on agro‐ecological service crops (ASCs, i.e break crops, living mulch) and organic compost application. This study was conducted to determine the effect of tillage, ASC termination, and compost rates on yield and soil N fertility in organic vegetable production in Central Italy. In a long‐term organic field, in a strip plot design, barley was cultivated before melon. Two termination strategies of barley (green manure–GM, flattening by the use of a roller crimper–RC) were compared with a control without barley (FA). Three compost application rates (0, 15, and 30 Mg ha − 1 ) were studied. While the compost rates did not show any difference among compared production parameters, the combined tillage–ASC termination strategy significantly increased melon yield in the GM compared with RC treatments, probably due to the lower soil temperature under the thick barley mulch. Soil mineral N (SMN) during the melon cycle was not a limiting factor for plant growth. Mean SMN values ranged from 22 for the 2012 RC and 36 mg kg −1 for the 2012 FA. High C and N inputs in barley treatments and high compost rates indicated an N surplus, which, in the medium–long term, could represent an N storage for subsequent crops in the rotation and potentially determine C sequestration. The results demonstrated that, to assure adequate yield, the ASC mulch based no‐tillage approach should follow the redesign of the whole cropping system, taking into account the entire suite of techniques of crop management.